Behavioral indicators of cattle housed in different shade surfaces availability completed in dry tropical environment - Castro-Pérez, B. I.; Portillo-Loera, J. J.; Estrada-Angulo, A.; Urías-Estrada, J. D.; Rivera-Méndez, C. R.; Mendoza-Cortez, D. A.; Plascencia, A.; Ríos-Rincon, F. G. (Diponegoro University, 2026)
The objective was to assess the behavioral indicators of cattle housed in different shade surface availabilities under dry tropical environmental conditions carried out in the summer-autumn period. During 63 days the usual social and agonist variables were recorded in 1,040 bulls housed in 16 pens (4 replicas/treatment, 65 bulls/pen). Ambient temperature (AT) and relative humidity (RH) were record-ed, and the humidity index (THI) was estimated. The shade surfaces tested were 1) conventional shade (S12%), 2) double shade (S24%), 3) shaded 100% without fans (S100), and 4) shaded 100% with fans (S100F). The average maximum value for AT, RH and THI was 38.1°C, 90.7% and 87.6 units. The shade surface influenced the proportion of animals under shade, eating, ruminating, and mounting, and decreased the proportion of animals panting. Pens S24 showed a higher proportion of animals eating and resting (quadratic component, P=0.05). Providing ventilation increased (P=0.01) 2.7 times the pro-portion of animals eating and decreased (P=0.01) 6.5 times the proportion of animals panting. At 0800h a greater proportion of animals eating and riding was observed, while from 1130h onwards the proportion of animals under shade, ruminating and resting increased. At 2:00 p.m., the highest percent-age of animals were panting. It is concluded that a shaded surface of 12% of the pen area is enough to alleviate behavioral patterns in animals under high environmental heat load. Shade plus ventilation was shown to be a strategy in reducing panting and increasing the proportion of animals in feed bunks.